Demoralisation and its associated factors among cancer patients in a university hospital / Chin Han Lim - Chin, Han Lim (2018)
Objective: To date, there is no literature on demoralisation in Malaysian patients with cancer. The primary objective of this study was to examine the relationship between demoralisation with positive emotion, depression, distress, sociodemographic, disease and treatment-related factors. The Demoralisation Scale had also been translated and validated into Malay language for the use of the Malaysian patients. Method: This was a cross-sectional study conducted in Universiti Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia with the approval from the Medical Ethics Committee was obtained. One hundred and seventy-eight subjects were recruited from the oncology and haematological ward, day-care clinics and follow-up clinics from January to December 2017 based on the inclusion and exclusion criteria. The convenient sampling method was employed. After obtaining the informed consent from the subjects, the sociodemographic and clinical data of the subjects were collected. The subjects filled both English and Malay versions of the Demoralisation Scales, Centre for Epidemiologic Studies Depression (CESD) Scale and Distress Thermometer. SPSS v24.0 was used as a method for statistical analysis. Descriptive analysis, Spearman’s correlation, chi-square test and multiple logistic regression were used to examine demoralisation and its associated factors. Principal component factor analysis, internal consistency test, intra-class correlation and receiver operating characteristic curve were used for the validation of DS-M. iii Results: The mean age of the subjects was 53.6± 16.51 years old (range 18-86). Sixty-four percent of the patients were female. In terms of race, most of the subjects were Chinese (42.1%), followed by Malays (39.9%) and others (18%). The commonest religion was Islam (41%), followed by Buddhism (27.5%) and Christianity (15.2%). About two fifths of the subjects had breast cancer, and twenty-four percent of the subjects were at the advanced stage of various cancer. The mean score for the Malay version of the Demoralisation Scale (DS-M) was 18.79 + 15.30. 37.6% of the cancer patients were demoralised based on DS-M score >23. In the group with high demoralisation, 61.2% were depressed (x2=72.76, p<0.01), 52.2% had low positive emotion (x2=41.34, p<0.01) and 68.7% were distressed (x2=40.45, p<0.01). On the other hand, in the group with low demoralisation, 95.5% were not depressed (x2=72.76, p<0.01), 91% had high positive emotion (x2=41.34, p<0.01) and 79.3% were not distressed (x2=40.45, p<0.01). Demoralisation was correlated positively with depression (r=.78, p<.01) and distress level (r=.64, p<0.01). Inverse relationship was found between demoralisation and positive emotion (r=-.69, p<.01). No significant association was found between demoralisation with sex ((x2=.09, p=.77), age (x2=.12, p=.74), race (x2=2.23, p=.14), religion (x2=2.97, p=.09), marital status (x2=.01, p=.95), employment status (x2=1.98, p=.16) and income (x2=1.93, p=.17). The association between demoralisation and the type of cancer (x2=.02, p=.90), stage of cancer (x2=.09, p=.77), duration since diagnosis (x2=.04, p=.85), mode of treatment (x2 =.41, p=.52), medical illness (x2 =1.12, p=.57) and psychiatric illness (x2=2.21, p=.14) were not significant as well. The principal component analysis of DS-M yielded four-factor structures. The Cronbach’s alpha for the total scale was .95, and the subscales ranged between 0.81-0.92. The Spearman’s correlation showed a good convergent validity between DS-M and Distress Thermometer (r=.64, p<0.05) and divergent validity between DS-M and PERS (r=-.69, iv p<.01). The AUC was 0.92 (SE: 0.02, p < 0.01, 95% CI 0.88-0.97). The optimal sensitivity and specificity for the DS-M were shown by the cut-off score of 23. Conclusion: Demoralisation was highly prevalent in Malaysian cancer patients. Depression and distress were significantly related to demoralisation. The lower level of positive emotion was found in the patient suffering high demoralisation and vice versa. The state of demoralisation among the cancer patients should receive more attention from the oncology and mental health teams. The validated Malay version of the demoralisation scale can be used on the Malaysians to screen for demoralisation and institute early intervention.